2015
DOI: 10.1007/s00268-015-3115-4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Surgical Site Infections Following Pancreatoduodenectomy

Abstract: Preoperative ERCP and stenting, end-to-side PJ and the presence of non-diabetic endocrine co-morbidity may result in a significantly higher risk of SSIs. Further studies targeting these patient subpopulations are warranted to enable a better understanding of how these factors contribute to the incidence of SSIs following PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…Various risk factors for SSI have been reported in recent studies, which are shown in Table 6. Many studies have demonstrated that preoperative biliary drainage [2,7,8,16,17,36,38] and pancreatic fistula [8,10,38] are independent risk factors for SSI, which is consistent with the present study. Previous studies [8,30,36] have reported that a high BMI is a risk factor for SSI, which is consistent with another study in the literature showing that overweight and obesity increase the risk of SSI in many types of surgery [39].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Various risk factors for SSI have been reported in recent studies, which are shown in Table 6. Many studies have demonstrated that preoperative biliary drainage [2,7,8,16,17,36,38] and pancreatic fistula [8,10,38] are independent risk factors for SSI, which is consistent with the present study. Previous studies [8,30,36] have reported that a high BMI is a risk factor for SSI, which is consistent with another study in the literature showing that overweight and obesity increase the risk of SSI in many types of surgery [39].…”
Section: Discussionsupporting
confidence: 93%
“…However, the morbidity rate remains high, particularly regarding SSI, which is one of the most common problems after PD. The incidence of SSI after PD varies from 12 to 51% [7,8,[15][16][17]. Many factors contribute to SSI, including multiple enteric anastomoses, extensive physiologic changes, blood loss, and a long operative time [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is associated with significant harm, including a 4 per cent risk of pancreatitis, haemorrhage and bowel perforation. Biliary colonization following ERCP has been reported to be as high as 27 per cent, with a resultant impact on surgical‐site infections after pylorus‐preserving pancreaticoduodenectomy (PPPD).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, postoperative wound infection delays adjuvant chemotherapy in patients with pancreatic cancer and doubles the risk of chemotherapy omission . Potential causative factors include malnutrition, preoperative biliary drainage, and surgery‐related variables such as main pancreatic duct diameter, POPF, and postoperative hemorrhage . The Surgical Care Improvement Project (SCIP) was created by the Centers of Medicare and Medicaid Services to decrease preventable SSIs .…”
Section: Discussionmentioning
confidence: 99%